Effect of gait training with body weight support in hemiparetic pacients balance - Yoneyama, Simone Minae; Silva, Thayssa Leão Nascimento da; Baptista, Josemberg da Silva; Mayer, William Paganini; Paganotti, Mônica Tanaka; Costa, Patrik Fontes (Revista de Medicina, 2009)
The Body Weight Support (BWS) was used for the first time in clinical studies by the 80s. It is believed that this therapy promotes improvement of gait in patients with Stroke sequel. We investigated the importance of gait training in treadmill with BWS in those patients. Seven patient with clinical diagnosis of hemiparesis or hemiplegia were randomly submitted to a treadmill training protocol with BWS, (Experimental, n=4), or to traditional approach without BWS (Control, n=3) for 20 sessions to balance evaluation. The balance evaluation by BERG scale showed significant improves on experimental group (p = 0,003). Further investigations should be conducted in order to elucidate those data obtained.